2022
DOI: 10.3390/risks10060114
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Behavioral Intentions to Use Islamic Financial Technology: An Empirical Assessment

Abstract: This study examines the antecedents/determinants of behavioral intentions toward the utilization of Islamic financial technology for Middle Eastern customers. The study applied structural equation modeling (PLS-SEM). After robust research efforts were invested in the identification of factors, they and were converted into measures, and the results were analyzed. The results demonstrate that the independent variables shown in the UTAUT model have a significant impact on the behavior to adopt Islamic financial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 60 publications
1
15
0
5
Order By: Relevance
“…Correspondingly, in Pakistan, religion has an active role in choosing Islamic banking (Butt et al , 2018). Recently, Khan et al (2022) demonstrated that behaviour in adopting Islamic financial technology indicates that individuals are inclined to use IF technology while making online transactions. In SMEs, AtIF is stumpy and displays negative AtIF.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Correspondingly, in Pakistan, religion has an active role in choosing Islamic banking (Butt et al , 2018). Recently, Khan et al (2022) demonstrated that behaviour in adopting Islamic financial technology indicates that individuals are inclined to use IF technology while making online transactions. In SMEs, AtIF is stumpy and displays negative AtIF.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Disrupsi keuangan syariah akibat fintech memunculkan pentingnya teknologi dalam sistem keuangan syariah (Miskam et al, 2019). Khan et al, (2022) menyatakan bahwa bidang keuangan Islam berkembang dan menarik perhatian secara global, bahkan diapresiasi oleh non-Muslim. Berdasarkan Global Islamic Finance Report (GIFR Press Release, 2021), industri jasa keuangan syariah global terus tumbuh dengan rata-rata 11,38% per tahun sejak 2019.…”
Section: Pendahuluanunclassified
“…Makna Islamic fintech menurut Nafiah & Faih, (2019) adalah perpaduan, perkembangan yang ada dalam uang dan inovasi yang bekerja dengan proses pertukaran dan usaha dalam pandangan nilai-nilai syariah. Menurut Khan et al, (2022), Islamic fintech didefinisikan dengan cara yang sama seperti conventional fintech, dengan perbedaan pada kepatuhan syariah. Ini adalah kombinasi dari dua kata, Islami dan fintech.…”
Section: Aspek Ontologi Islamic Fintechunclassified
“…In the field of Islamic accounting, the future work could be used for Financial Technology (Fintech) such as Regtech, InsureTech and asset management (Atif et al, 2021b;Khan and Rabbani, 2020;Rabbani et al, 2020) and big data (Sun et al, 2020) in Sharia governance of Islamic financial institutions. Fintech is the use of disruptive technology for the enhancement of financial services, and more research is needed to see the impact of these technologies in improving the accounting and Sharia governance practices (Khan et al, 2022;Rabbani et al, 2022Rabbani et al, , 2021aRabbani et al, , 2021bRabbani et al, , 2021c. Further research can also be conducted on accounting information technology to make accounting and Sharia governance more automated and transparent.…”
Section: Conclusion and Future Research Directionsmentioning
confidence: 99%